Managing arsenic in the environment : from soil to human health - Naidu, R. (CSIRO ; [Distributed in North America by] Science Publishers, 2006)
Arsenic is one of the most toxic and carcinogenic elements in the environment. This book brings together the current knowledge on arsenic contamination worldwide, reviewing the field, highlighting common themes and pointing to key areas needing future research.